Theoretical validation of some third-generation epidermal growth factor receptor (EGFR) Inhibitors as non-small cell lung cancer (NSCLC) drugs. Issue 1 (31st December 2023) - Ibrahim, Muhammad Tukur; Uzairu, Adamu
ABSTRACT: The most common and lethal type of lung cancers with close to 1.8 million cases and less than 20% survival rate after diagnosis was the NSCLC. It also accounted for about 80% to 85% of the reported lung cancer cases. To combat this problem, more effective NSCLC drugs are needed. Molecular docking-based virtual screening was performed to provide a firsthand information on the binding modes between the AZD9291 derivatives and the EGFR receptor. The docking-based virtual screening has identified six compounds (17, 12, 15 1, 10 and 19) as the hit with compound 17 as the best hit with a mole dock score of -151.71 kcal/mol, respectively. It interacted with these group of amino acids ASP800 (2.26Å), PRO794 (2.87Å), MET793 (2.29Å) and CYS797 (2.65Å) using hydrogen bond, and with LEU799, ARG841(4), PHE723, LEU718 and CYS797 group of amino acids using hydrophobic interaction, respectively. All the hit compounds recognized were realized to have better mole dock scores than the Osimertinib (AZD9291) with a mole dock score of -118.87 kcal/mol. The hit compounds were ascertained to be drug-like and possessed good pharmacokinetic profiles. The value of their bioavailability score (0.55) further confirmed that they are orally bioavailable.